The Effect of 2% Chitosan Oligosaccharides and 15% EDTA on Calcium Loss in the Root Canal - Abidin, Trimurni; Geovani, Gina (Journal of Syiah Kuala Dentistry Society, 2023)
Background: During instrumentation and irrigation, the composition of the dentin structure can be dissolved. Currently, the most widely used irrigation and chelating material are EDTA, which has the disadvantage of causing dentin erosion which reduces the hardness of the dentin, so that oligosaccharide chitosan is developed, which is more biocompatible and easier to manipulate as an irrigant material. This study aimed to evaluate whether there was a change in the concentration of calcium ions after treatment with chitosan oligosaccharide gel and EDTA gel using atomic absorption spectrophotometry. Materials and Methods: For 32 mandibular premolars, instrumentation, and irrigation were performed, and then chelation material was divided into two groups, namely the group with 2% chitosan oligosaccharide and 15% EDTA gel chelation material. Then the calcium ions in both groups will be measured using atomic absorption spectrophotometry. Results: There was a significant difference in calcium ion loss in root canal dentin after applying 2% chitosan oligosaccharide gel chelating agent and 15% EDTA gel at different times for 5 minutes, p-value = 0.021 (p0.05). Conclusion: 2% oligosaccharide chitosan can be a chelating agent when developed as a gel, affecting calcium ion loss. The 2% chitosan oligosaccharide resulted in the lowest average loss of calcium ions.